2014
DOI: 10.1016/j.spinee.2014.05.022
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of blood loss in adolescent idiopathic scoliosis

Abstract: Background contextPrevious studies have shown that modern

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 31 publications
2
15
0
1
Order By: Relevance
“…Another pillar of PBM is the preoperative identification of patients who are at risk of receiving perioperative blood transfusion. Several predictors have been suggested in relation to the risk of blood loss or transfusion in AIS, including age, sex, curve magnitude, duration of surgery, low preoperative hemoglobin (Hb), fusion length, and surgical expertise . However, results are contradictory, and the clinical applicability is not well established, because studies vary in methodology and primary endpoints.…”
Section: Objectivementioning
confidence: 99%
“…Another pillar of PBM is the preoperative identification of patients who are at risk of receiving perioperative blood transfusion. Several predictors have been suggested in relation to the risk of blood loss or transfusion in AIS, including age, sex, curve magnitude, duration of surgery, low preoperative hemoglobin (Hb), fusion length, and surgical expertise . However, results are contradictory, and the clinical applicability is not well established, because studies vary in methodology and primary endpoints.…”
Section: Objectivementioning
confidence: 99%
“…Transfusion requirements are directly related to blood loss in correction of paediatric spinal deformities which may be determined by the severity of the preoperative Cobb angle and the number of fused vertebral segments relative to the patient's weight; however, not all studies have shown an increased risk of transfusion with greater numbers of fused vertebrae [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying those patients at risk for increased blood loss or transfusion is a critical and elusive goal in these surgeries. Many of the identified risk factors for bleeding or transfusion in these surgeries are relatively unalterable preoperative demographics or required surgical constraints . These include surgical duration, Cobb angle, and patient weight.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the identified risk factors for bleeding or transfusion in these surgeries are relatively unalterable preoperative demographics or required surgical constraints. 3,[12][13][14][15][16][17] These include surgical duration, Cobb angle, and patient weight. Directly increasing red blood cell mass with preoperative erythropoietin may be used, but this is not routinely practiced in our institution due to time and geographical restraints, the increased need for frequent preoperative monitoring of red cell mass and FDA black box warning for perisurgical administration.…”
Section: Introductionmentioning
confidence: 99%